Yttrium‐90 radioembolization for intermediate‐advanced hepatocellular carcinoma: A phase 2 study. Issue 5 (22nd March 2013) - Mazzaferro, Vincenzo; Sposito, Carlo; Bhoori, Sherrie; Romito, Raffaele; Chiesa, Carlo; Morosi, Carlo; Maccauro, Marco; Marchianò, Alfonso; Bongini, Marco; Lanocita, Rodolfo; Civelli, Enrico; Bombardieri, Emilio; et al.
Abstract: Yttrium‐90 radioembolization (Y90RE) is a novel approach to radiation therapy for hepatocellular carcinoma (HCC), never tested in phase 2 studies. Fifty‐two patients with intermediate (n.17) to advanced (n.35) HCC were prospectively recruited to assess, as the primary endpoint, efficacy of Y90RE on time‐to‐progression (TTP). Secondary endpoints were tumor response, safety, and overall survival (OS). All patients were Eastern Cooperative Oncology Group (ECOG) score 0‐1, Child‐Pugh class A‐B7. Y90RE treatments aimed at a lobar delivery of 120 Gy. Retrospective dosimetric correlations were conducted and related to response. Fifty‐eight treatments were performed on 52 patients. The median follow‐up was 36 months. The median TTP was 11 months with no significant difference between portal vein thrombosis (PVT) versus no PVT (7 versus 13 months). The median OS was 15 months (95% confidence interval [CI], 12‐18 months) with a nonsignificant trend in favor of non‐PVT versus PVT patients (18 versus 13 months). Five complete responses occurred (9.6%), and the 2 year‐progression rate was 62%. Objective response was 40.4%, whereas the disease control rate (78.8%) significantly affected survival (responders versus nonresponders: 18.4% versus 9.1%; P = 0.009). Tumor response significantly correlated with absorbed dose in target lesions ( r = 0.60, 95% CI, 0.41‐0.74, P < 0.001) and a threshold of 500 Gy predicted response (area under the curve, 0.78). Mortality at 30‐90 days was 0%‐3.8%. Various grades of reduction in liver function occurred within 6 months in 36.5% of patients, with no differences among stages. On multivariate analysis, tumor response was the sole variable affecting TTP ( P < 0.001) and the second affecting survival (after Child‐Pugh class). Conclusion: Y90RE is an effective treatment in intermediate to advanced HCC, particularly in the case of PVT. Further prospective evaluations comparing Y90RE with conventional treatments are warranted. (HEPATOLOGY 2013)